2003
DOI: 10.1002/jcb.10608
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic tensile stretch modulates proteoglycan production by intervertebral disc annulus fibrosus cells through production of nitrite oxide

Abstract: Degeneration of the intervertebral disc is the main pathophysiological process implicated in low back pain and is a prerequisite to disc herniation. Clinically, mechanical forces are important modulators of the degeneration, but the underlying molecular mechanism is not known and needs investigation to identify the biological target. The aim of this work was to study, at the molecular level, the effects of cyclic tensile stretch (CTS) on the production of proteoglycan by intervertebral disc annulus fibrosus ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
61
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(66 citation statements)
references
References 45 publications
5
61
0
Order By: Relevance
“…Excessive NO may directly disturb ER function and activate ER stress pathway [14,17,40]. Here, we demonstrated significant increase of NO production and iNOS mRNA in rat AF cells exposed to cyclic stretch, which was consistent with previous studies showing that NO were up-regulated by the stimulation of prolonged cyclic stretch in AF cells [2,33]. NO overproduction appears to occur before the onset of ER stress and subsequent apoptosis, thus it is conceivable that NO production is a potential trigger of ER stress observed in rat AF cells during cyclic stretch.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Excessive NO may directly disturb ER function and activate ER stress pathway [14,17,40]. Here, we demonstrated significant increase of NO production and iNOS mRNA in rat AF cells exposed to cyclic stretch, which was consistent with previous studies showing that NO were up-regulated by the stimulation of prolonged cyclic stretch in AF cells [2,33]. NO overproduction appears to occur before the onset of ER stress and subsequent apoptosis, thus it is conceivable that NO production is a potential trigger of ER stress observed in rat AF cells during cyclic stretch.…”
Section: Discussionsupporting
confidence: 92%
“…For instance, endoplasmic reticulum stress triggered by NO overproduction, leads to b-cell apoptosis via CHOP induction and caspase-12 activation [29]. Furthermore, cyclic stretch can induce NO overproduction [2,33] and even cause apoptosis [34] in AF cells. These data suggest that NO may participate in force-induced signals into apoptotic responses by endoplasmic reticulum stress.…”
Section: Introductionmentioning
confidence: 99%
“…Cell membrane stretch due to cell flattening activates ion channels and induces alterations in membrane potential and hence affects the cell metabolism [11,81]. The stretching of rabbit AF cells (5% elongation or 15% area change) has been shown to increase nitric oxide production, to decrease proteoglycan production and to increase apoptosis of AF cells [8,96,97]. However, a 2% cyclic strain applied on human AF cells was shown to increase aggrecan and decrease matrix metalloproteinase (MMP) gene expression [85].…”
Section: Direct Stimulusmentioning
confidence: 99%
“…These forces remain in the NP and dissipate into adjacent IVDs through the stiff vertebral body. Previous studies have shown that the strain resisted by the OAF is between 1 and 13% (Broberg, 1983;Klein et al, 1983;Ebara et al, 1996;Rannou et al, 2003).…”
Section: Introductionmentioning
confidence: 99%